Characterization of Fibrous Insulating Materials in their Application in Dynamic Insulation Technology. (November 2015) - Alongi, Andrea; Mazzarella, Livio
Abstract: Previous studies dealing with dynamic insulation technology neglect the microscopic interaction between the solid matrix of the porous material and the air flowing through the pore structure. The main goal of this work is to investigate this interaction, and its effects on the heat transfer phenomena at macroscopic scale using the Volume Average Method. At first, the microscopic geometry of two samples of rock wool is investigated through image analysis, leading to the evaluation of porosity and granulometry. Then, the volume averaging technique is applied to the microstructure of fibrous materials. Thermal dispersion and thermal tortuosity are introduced and evaluated through numerical simulations of simplified geometry in laminar and low-Pe conditions, and two regression equations are defined.